IFRS adoption and CEO compensation: evidence from listed banks in Nigeria - Stephen Ojeka; Alex Adegboye; Dorcas Titilayo Adetula; Kofo Adegboye; Inemesit Udoh (Banks and Bank Systems, 2019)
The study investigates the influence of International Financial Reporting Standards adoption, using accounting performance measure, to determine the CEO pay in listed banks in Nigeria. The audited annual financial statements of listed banks in Nigeria covering the period of 2009–2015 are analyzed. Fixed effect model, viz panel data analysis is adopted to establish the findings. The findings indicate that adoption of IFRS in Nigeria results in an inverse relationship with accounting performance in determining the CEO compensation after controlling for firm and corporate governance mechanism. However, the adoption of IFRS shows significant positive influence on the CEO pay. This result has policy implication, which encourages the regulatory agencies like Central Bank of Nigeria to monitor the compliance of all banks in Nigeria to the IFRS adoption.